Physical education today: bet on a new conception (Impetus, 2021)
The current demand for education is directed towards the search for new trails that allow people an interaction in thesociety from their different capacities and abilities, all this according to the needs and characteristics that understand the performance scenarios in the world modern. This social demand must be assumed by multiple institutions and entities that contribute inthe formation of individuals; the school is part of said challenge, which must be assumed from the multiplicities that composes and demands the society of the XXI century.